Equipment power consumption and load factor profiles for buildings' energy simulation (ASHRAE 1742-RP). (26th November 2018) - Omer Sarfraz,; Bach, Christian K.
Abstract : In most office buildings, plug loads are one of the main contributors to the building's overall energy consumption and therefore need to be considered in load calculations. The heat gains from different office equipment deviate from their peak values due to both user and equipment behavior. The variation in the heat gains of different office equipment can be presented by average weekday and weekend power consumption profiles. These power consumption profiles serve as an input to the energy simulation programs for the purpose of load calculation. In this article, weekday and weekend power consumption profiles are developed for different office equipment. In addition, load factor profiles are developed for some typical office spaces and are compared against the peak load factors listed in the ASHRAE Handbook of Fundamentals (2017). Recommendations for the minimum number of testing days necessary to obtain the equipment peak heat gain are also made.